2019
DOI: 10.1111/beer.12227
|View full text |Cite
|
Sign up to set email alerts
|

Do employees value strategic CSR? A tale of affective organizational commitment and its underlying mechanisms

Abstract: Virtually all studies that focus on the relationship between CSR perceptions and employees’ organizational commitment have not taken into consideration the fit between social and environmental activities and a firm’s business‐unit strategy. This is essential to inquire because scholars have argued that when companies ingrain CSR activities into their strategy‐making process (i.e., in their vision, mission, and overall business model), this might send a more compelling message that resonates closer to workers’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 131 publications
(391 reference statements)
0
68
0
1
Order By: Relevance
“…Reflecting certain attributes that are valued by external stakeholders contributes to the identity development of organization members and enhances employees' sense of importance and value (Chaudhary & Akhouri, 2019; Dutton & Dukerich, 1991; Kim, Lee, Lee, & Kim, 2010). Working in a business with high reputation contributes to employees' positioning themselves in a good place in their social environment, and it rises employees' self‐esteem (Rodrigo, Aqueveque, & Duran, 2019). Supporting those theoretical arguments, previous studies indicated that companies' CSR practices positively affect employees' external prestige perception (De Roeck & Delobbe, 2012; Gürlek & Tuna, 2019).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Reflecting certain attributes that are valued by external stakeholders contributes to the identity development of organization members and enhances employees' sense of importance and value (Chaudhary & Akhouri, 2019; Dutton & Dukerich, 1991; Kim, Lee, Lee, & Kim, 2010). Working in a business with high reputation contributes to employees' positioning themselves in a good place in their social environment, and it rises employees' self‐esteem (Rodrigo, Aqueveque, & Duran, 2019). Supporting those theoretical arguments, previous studies indicated that companies' CSR practices positively affect employees' external prestige perception (De Roeck & Delobbe, 2012; Gürlek & Tuna, 2019).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In particular, employees, as one of the most important stakeholder groups in an enterprise, and who have tacit knowledge of the organisation, tend to be more aware of the motives behind CSR than other stakeholders (Fryzel & Seppala, ). Therefore, the way in which employees are psychologically affected by CSR activities is deserving of researchers’ and managers’ keen attention, since these psychological effects, such as organisational commitment, have the potential to decrease staff turnover and have positive effects on productivity (Rodrigo, Aqueveque, & Duran, ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, strategic CSR emphasizes the coexistence of commercial and social benefits [2,41,42]. Porter and Kramer [43] promote the concept of "strategic charity," arguing that social and economic objectives can be linked in the long term.…”
Section: Definitions and Characteristics Of Strategic Csrmentioning
confidence: 99%
“…A high degree of competition in a product market will reinforce the firm's strategic consideration in the implementation of CSR [55]. Several studies also find that the pressure of competition forces firms to think highly of stakeholders and improve their CSR performance related to consumers and employees [1,42,53].…”
Section: Impact Of Product Market Competition On Strategic Csrmentioning
confidence: 99%
See 1 more Smart Citation